Memorising Contemporary Piano Music as Described by Professional Pianists. (November 2022) - Fonte, Vera; Pipa, Luís; Williamon, Aaron; Lisboa, Tania
The convention of performing from memory is a well-established practice among pianists, but an exception is often made for contemporary piano repertoire. Even so, a number of renowned pianists continue performing highly demanding compositions of this genre from memory, and this practice is commended by contemporary composers. No research to date has systematically investigated musicians' views on this matter and explored detailed accounts of how to prepare and memorise such repertoire. In this study six renowned professional pianists with experience in performing contemporary piano repertoire were interviewed on their approaches to learning and memorising this music. Interpretative Phenomenological Analysis of the pianists' accounts revealed a variety of views on performing contemporary music from memory, with some pianists advocating benefits from performing by heart and others from using the score. The general practice strategies reported resembled approaches described by skilled musicians in relation to standard repertoire, with some variations related to different types of contemporary music styles. Memorisation accounts emphasised the importance of strategies such as mental rehearsal, chunking, and reliance on different types of memory and their combination.